QUALITY EVALUATION OF SMOKED FLYING FISH (Hirundichthys oxycephalus) THROUGH TOTAL PLATE COUNT METHOD AT THE SOMBA CULINARY TOURISM CENTER, MAJENE - Nurfadilah, Nurfadilah; Yulia, Irma; Maruka, Safriyanto S.; Wiranto, Edi; Irpan, Irpan; Rosmina, Rosmina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
The process of processing smoked fish that does not pay attention to sanitation and hygiene standards, as well as open storage next to the road body, causes dust, germs, and bacteria to contaminate the quality of processed smoked flying fish in the Somba culinary tourism center. This study aims to evaluate the microbiological quality of smoked flying fish based on Total Plate Count (ALT) and water content to assess its compliance with food safety standards. This study used a combination method of sequential exploratory model, which is a combination research method that combines qualitative and quantitative research methods sequentially. Data collection was carried out by purposive sampling, and the parameters for this sampling were based on the 10 stalls with the most production and customers. The results showed that out of 10 samples, there were only four samples that met the SNI requirements of a maximum of 1.0×105 colonies/g, including samples S2 (2.74×104), S5 (2.53×104), S9 (2.33×104) and S10 (2.38×104). In contrast, the results of the water content test show that out of 10 samples, there are only three smoked flying fish samples that have a water content value that matches the maximum limit of smoked fish based on SNI, which is a maximum of 60% including samples S2, S5, and S9